Bioinspired Precision Engineering of Three‐Dimensional Epithelial Stem Cell Microniches. Issue 6 (24th April 2020) - Prina, Elisabetta; Amer, Mahetab H.; Sidney, Laura; Tromayer, Maximilian; Moore, Jonathan; Liska, Robert; Bertolin, Marina; Ferrari, Stefano; Hopkinson, Andrew; Dua, Harminder; Yang, Jing; Wildman, Ricky; et al.
Abstract: Maintenance of the epithelium relies on stem cells residing within specialized microenvironments, known as epithelial crypts. Two‐photon polymerization (2PP) is a valuable tool for fabricating 3D micro/nanostructures for stem cell niche engineering applications. Herein, biomimetic gelatin methacrylate‐based constructs, replicating the precise geometry of the limbal epithelial crypt structures (limbal stem cell "microniches") as an exemplar epithelial niche, are fabricated using 2PP. Human limbal epithelial stem cells (hLESCs) are seeded within the microniches in xeno‐free conditions to investigate their ability to repopulate the crypts and the expression of various differentiation markers. Cell proliferation and a zonation in cell phenotype along the z ‐axis are observed without the use of exogenous signaling molecules. Significant differences in cell phenotype between cells located at the base of the microniche and those situated towards the rim are observed, demonstrating that stem cell fate is strongly influenced by its location within a niche and the geometrical details of where it resides. This study provides insight into the influence of the niche's spatial geometry on hLESCs and demonstrates a flexible approach for the fabrication of biomimetic crypt‐like structures in epithelial tissues. This has significant implications for regenerative medicine applications and can ultimately lead to implantable synthetic "niche‐based" treatments. Abstract : A precision‐engineered microniche mimicking the epithelial stem cell niche of the corneal limbus is microfabricated from GelMA‐based hydrogels alone by two‐photon polymerization and used to study the influence of 3D architecture on cell differentiation. Zonation of marker expression along the z ‐axis demonstrated that spatial geometry influenced cell phenotype within this microniche in vitro, without the need for exogenous signaling molecules.